Association of increased CCL5 and CXCL7 chemokine expression with neutrophil activation in severe stable COPD. Issue 11 (23rd August 2009) - Di Stefano, A; Caramori, G; Gnemmi, I; Contoli, M; Bristot, L; Capelli, A; Ricciardolo, F L M; Magno, F; D'Anna, S Ennio; Zanini, A; Carbone, M; Sabatini, F; et al.
Abstract : Background: Increased numbers of activated neutrophils have been reported in the bronchial mucosa of patients with stable chronic obstructive pulmonary disease (COPD), particularly in severe disease. Objectives: To investigate the expression of neutrophilic chemokines and adhesion molecules in bronchial biopsies from patients with stable COPD of different severity (GOLD stages I–IV) compared with age-matched control subjects, smokers with normal lung function and never smokers. Methods: The expression of CCL5, CXCL1, 5, 6, 7 and 8, CXCR1, CXCR2, CD11b and CD44 was measured in the bronchial mucosa using immunohistochemistry, confocal immunofluorescence, real-time quantitative polymerase chain reaction (RT-QPCR) and Western blotting (WB). Results: The numbers of CCL5+ epithelial cells and CCL5+ and CXCL7+ immunostained cells were increased in the bronchial submucosa of patients with stable severe COPD compared with control never smokers and smokers with normal lung function. This was also confirmed at the level of mRNA expression. The numbers of CCL5+ cells in the submucosa of patients with COPD were 2–15 times higher than any other chemokines. There was no correlation between the number of these cells and the number of neutrophils in the bronchial submucosa. Compared with control smokers, the percentage of neutrophils co-expressing CD11b and CD44 receptors was significantly increased in the submucosa of patients with COPD. Conclusion: The increased expression of CCL5 and CXCL7 in the bronchial mucosa of patients with stable COPD, together with an increased expression of extracellular matrix-binding receptors on neutrophils, may be involved in the pathogenesis of COPD.